Constructed Wetland sebagai Upaya Pengurangan Konsentrasi Beban Organik pada Limbah Cair Rumah Potong Hewan - Achmad Chusnun Ni'am; Nadia Rana Abiyya Kholish; Deni Halim Trihandana (Prosiding ESEC, 2023)
The existence of slaughterhouses is important to fulfill the need for animal protein for consumers. Every day, slaughterhouses produce waste from their activities. The liquid waste generated contains high organic load. In this study, we focused on a constructed wetland system with Typha angustifolia plant as a phytoremediation medium to treat slaughterhouse wastewater. This plant was studied for its ability to remove the organic load of slaughterhouse wastewater in terms of BOD, COD, TSS, and NH3N parameters. This research begins with the construction of a reactor in the form of a container box with a size of 20cm x 21cm x 31cm which will be filled with soil (10cm), silica sand (2cm), and gravel (2cm). Acclimatization is carried out to enter the range finding test experiment, where the concentration of effluent exposure used is 25%, 50%, and 75% for a period of 7 days. Data analysis aims to compare the water quality in the reactor using the overal efficiency equation, which is then continued with the Anova test. Based on the research that has been done, Typha angustifolia succeeded in removing BOD by 97.90%, COD 98.95%, TSS 94.09%, and NH3N 94.61%. Anova test showed that concentration and detention time did not affect the effectiveness of plants in reducing waste.